FENOMENA BODYSHAMING PADA MAHASISWI BKI IAIN SURAKARTA - Putri, Yoan Rachmawati; Lessy, Zulkipli (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
The behavior known as "body shaming" is often taken for granted. Many people believe that it is acceptable to comment about other people's bodies and physical appearance; however, they do not understand that their actions can harm another person or contribute to the development of psychological disorders in that person. Each person is unique, and one of the distinguishing characteristics of him/her is his/her freedom to choose his/her own body, including the right to be fat, thin, or any other body type. The purpose of this study was to determine the phenomenon of body shaming among Bimbingan Konseling Islam (BKI) female students of class 2017 at IAIN Surakarta (now UIN Raden Mas Said). This study used a qualitative descriptive technique. The four women who volunteered to participate in the study were all familiar with the idea of shame. Data collection methods used in this study were interviews, observations, and questionnaires. The findings reveal that (1) bullying is similar to body shaming, (2) body shaming can prohibit people from participating in social activities because it makes them feel insecure, and (3) negative responses to body shaming can cause unpleasant sensations. Keywords: Body Shaming, Students of IAIN Surakarta, Phenomenon.